2017
DOI: 10.1108/ijchm-02-2016-0069
|View full text |Cite
|
Sign up to set email alerts
|

Identifying antecedents and outcomes of festival satisfaction

Abstract: Purpose This study aims to explore the relationships among antecedents (i.e. quality) and outcomes (i.e. trust, support, theme awareness and extension effect) of satisfaction at the 2013 Osong Cosmetics & Beauty (C&B) Expo held in Korea. Design/methodology/approach An onsite survey with self-administered questionnaires was administered for this study. A structural equation modeling (SEM) technique was used to analyze the relationships among ten constructs in the research model. Findings The results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 52 publications
3
15
0
Order By: Relevance
“…It was also found that TS (H5a) and ET (H5b) are significantly related to EE. Consistent with the results of Song et al (2017), TS during the event enhances tourists' awareness and perception of the Grand Prix, thus producing EE. ET has less effect than TS on EE, which indicates that tourists are more likely to lose their sense of trust after the Grand Prix.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…It was also found that TS (H5a) and ET (H5b) are significantly related to EE. Consistent with the results of Song et al (2017), TS during the event enhances tourists' awareness and perception of the Grand Prix, thus producing EE. ET has less effect than TS on EE, which indicates that tourists are more likely to lose their sense of trust after the Grand Prix.…”
Section: Discussionsupporting
confidence: 83%
“…From the perspective of co-branding, a local festival or event plays an important role in building relationships with other brands; in other words, EE is highly relevant to sport tourism events. Song et al (2017) indicated that an EE had a significant impact on the Osong C&B expo, leading customers to buy products during the festival and remember the brands from the festival after the event ended. Similarly, Song et al (2017) demonstrated that TS positively influences theme awareness, which positively influences the EE.…”
Section: Extension Effectmentioning
confidence: 99%
See 2 more Smart Citations
“…First, within the context of a mega-event, it not only shows the multidimensionality of event experience and event satisfaction but also proves that event experience is mostly affected by sense and feelings, which underlines the importance of engaging visitors in entertainment activities (Fu et al, 2020;Park and Park, 2017;Van Niekerk, 2017). Second, it is also in line with some previous studies (Fu et al, 2019;Lee et al, 2017;Song et al, 2017;Swart et al, 2018) by showing a positive relationship between positive satisfaction with the event and the destination, which represents a useful contribution to extant event research by bridging visitors' experiential response to an event with destination marketing in a broader context. This result should encourage researchers to further explore how host destinations of events can design experiences to influence future (re)visit intentions and positive word-ofmouth.…”
Section: Theoretical Implicationssupporting
confidence: 87%